Recommendations from the Brazilian Society of Anesthesiology (SBA) for difficult airway management in pediatric care - Lima, Luciana Cavalcanti; Cumino, Débora de Oliveira; Vieira, Alex Madeira; Silva, Cláudia Helena Ribeiro da; Neville, Mariana Fontes Lima; Marques, Felipe Oliveira; Quintão, Vinicius Caldeira; Carlos, Ricardo Vieira; Fujita, Ana Carla Giosa; Barros, Hugo Ítalo Melo; Garcia, Daniela Biachi; Ferreira, Cynthia Beatriz Tostes; et al. (Elsevier, 2024)
Difficult airway management in pediatrics during anesthesia represents a major challenge, requiring a careful approach, advanced technical expertise, and accurate protocols. The task force of the Brazilian Society of Anesthesiology (SBA) presents a report containing updated recommendations for the management of difficult airways in children and neonates. These recommendations have been developed based on the consensus of a panel of experts, with the objective of offering strategies to overcome challenges during airway management in pediatric patients. Grounded in evidence published in international guidelines and expert opinions, the report highlights crucial steps for the appropriate management of difficult airways in pediatrics, encompassing assessment, preparation, positioning, pre-oxygenation, minimizing trauma, and, paramountly, the maintenance of arterial oxygenation. The report also delves into additional strategies involving the use of advanced tools, such as video laryngoscopy, flexible intubating bronchoscopy, and supraglottic devices. Emphasis is placed on the simplicity of implementing the outlined recommendations, with a focus on the significance of continuous education, training through realistic simulations, and familiarity with the latest available technologies. These practices are deemed essential to ensure procedural safety and contribute to the enhancement of anesthesia outcomes in pediatrics.
Keywords: Airway management; Consensus; Difficult airway; Intubation; Laryngoscopy; Neonate; Pediatric anesthesia